Phytoremediation as a Tool to Remove Drivers of Antimicrobial Resistance in the Aquatic Environment - Kaniz F. Chowdhury; Rebecca J. Hall; Alan McNally; Laura J. Carter (Reviews of Environmental Contamination and Toxicology, 2023)
Antimicrobials, heavy metals, and biocides are ubiquitous contaminants frequently detected in water bodies across the globe. These chemicals are known as drivers of antimicrobial resistance (AMR), as these chemicals can select for resistance. Tools and processes, are therefore, needed to remove these chemicals from the environment to tackle the environmental component of AMR. Aquatic phytoremediation is a nature-inspired green solution to remove contaminants from the environment. Phytoremediation utilises macrophytes’ ability to sequester and degrade chemical pollutants in aquatic environments. In this review, we define the problem statement by highlighting the presence of AMR drivers in the aquatic environment. We also provide an in-depth review of phytoremediation to tackle chemical pollution by evaluating mechanisms for the removal and degradation of chemicals. This review identifies potential hyper-accumulators and understands how plant species and chemical composition can influence the potential for accumulation. Different pollutants accumulate to different extents in a range of aquatic macrophytes. Therefore, the combined use of floating, submerged and emergent plants would facilitate the optimum removal of AMR drivers considered in this review. A suggested configuration includes Helianthus annus around the edge of a contaminated site, followed by a belt of submerged plants ( Myriophyllum aquaticum ) and a bed of floating plants (e.g., Lemna species) together with the hyperaccumulator, Phragmites australis . Whilst phytoremediation offers a promising option to treat contaminated water, several critical knowledge gaps still exist. The effect of co-exposure to contaminants on the accumulation potential of plants and the fate of antibiotic-resistant genes and bacteria during the phytoremediation process are highlighted in this review. Based on this understanding, targeted areas for future research are proposed.